Agrobacterium tumefaciens medicated genetic transformation in Hevea - Jayashree R; Kala R G; Kumari Jayasree P; Rekha K; Sobha S; Sushamakumari S; Thanseem I***************** (Placrosym XIV, 2000, Hyderabad, India : Programme and Abstracts)
A method for Agrobacterium tumefaciens medicated genetic transformation in Hevea brasiliensis have been developed. This paper reports an effective method for the Agrobacterium tumefaciens medicated genetic transformation of Hevea brasiliensis with the plasmid vector containing B-glucuronidase as reporter gene, npt II gene for kanamycin resistance as the selectable marker and the sequence coding for SOD under the control of CaMV355 promotor.
Keywords: Agrobacterium tumefaciens; Genetic transformation; Hevea